Editors's Introduction to the Special Issue on "Grid, Cloud and Sky Applications for Knowledge-based Industries and Businesses" (Informatica, 2025)
Editors's Introduction to the Special Issue on "Grid, Cloud and Sky Applications for Knowledge-based Industries and Businesses"